A comparative study among different methods of detection of colistin resistant gram negative bacilli in a tertiary care hospital - Poonam AR; Bilolikar AK; Sahu S (Journal of Medical and Scientific Research, 2020)
Background: Multi-drug resistant gram negative bacteria (MDR GNB) have become a major health challenge worldwide. Colistin has an excellent bactericidal activity against these MDR GNB. However, Colistin resistance has been reported globally.